Językowe sposoby wyrażania punktu kulminacyjnego w opowiadaniach potocznych - Wyrwas, Katarzyna (Stylistyka, 2019)
The turning point in the everyday narratives may be signaled in several ways. Lexical exponents of complicating action are adverbs or adverbial phrases, which indicate the rate of speed, urgency of action and shortness of the period preceding the performance of the stock and the lack of preparation for its implementation. The climax of the story can be highlighted by the onomatopoeic words indicating the rate of unfolding events. The turning point may be signaled in compound sentences, which distinctly oppose events before the climax with events of climax. The climax of the story can also be indicated inflexionally by changing the past forms to historical present. Present fonns serve to emphasize the drama and events of impending danger and highlight change of situation. An important feature is that historical present forms provide delimitation in conversational narrative: present tense forms occurring alternately with the forms of the past tense is used to separate each subsequent event from other event, allow speaker to organize the story in chronological following segments.The complicating action in colloquial stories is emphasized also phonetically: due to changes in accentuation and intonation. Full sentence pitch playing a special role by enhancement of the selected word in a sentence, in this case by extending the accented vowels. Also rising pitch observed in complicating action parts maintains a high level of listeners interest and tension. Listeners are interpreting rising pitch as a announcement of further string of text.In addition to the factors mentioned, in the expressive, lively „acting out” of history narrators use such dramatization signals as short sentences, verbs elliptic or replace their onomatopoeic words. This makes the complexity of action and a turning point clearly defined, effectively engaging the attention and emotions of the audience.